Real or Imagined Controversies? A Climate Law Perspective on the Growing Links between the International Trade and Climate Change Regimes - Kulovesi, Kati (NLUJ, 2014)
Substantive overlap between the UNFCCC and the WTO legal regimes is already considerable and such links can be expected to increase if governments undertake serious efforts to achieve the global climate target of limiting temperature increase to below 2°C from pre-industrial times. The article seeks to challenge scholarship which tends to approach the relationship between the WTO and UNFCCC with a focus on such (currently non-existent) climate policies that are potentially problematic from the point of view of WTO law. It highlights that while trade bans and border carbon adjustments targeting processes and production methods feature among the most prominent topics in the academic debate, there are currently no concrete examples of such climate policies. The article emphasizes that a focus on potential conflicts risks conveying the false impression that climate policies are typically problematic viewed from the WTO perspective. The author also argues that the most common climate policies affecting international trade, such as energy efficiency requirements, can often be designed and implemented in a way that is fully compatible with WTO law. Finally, the article highlights the important role that renewable energy is estimated to play in achieving the global 2°C climate target. It argues that this is an area where links between the WTO and climate policies have been most pronounced thus far, as illustrated by the recent surge of WTO dispute settlement consultations and anti-dumping disputes relating to the use of renewable energy.